INTERFERENSI BAHASA BETAWI DALAM CERPEN MAHASISWA JURUSAN PBSI FITK UIN SYARIF HIDAYATULLAH JAKARTA - Siti Sahara (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
This study tried to see how far the interference of Betawi language in Department of  Education  Indonesian  Language  and  Literature  students’  short  story,  Faculty  of Tarbiya and Teaching Sciences, Syarif Hidayatullah State Islamic University of Jakarta? It would be interesting to make a research about it, because the location of the campus, located on the border between Jakarta and Tangerang, Banten. Therefore the researcher assumed it would be found the Betawi language interference in students’ short story.The  method  of  this  research  is  combining  quantitative  and  qualitative. Quantitative used to see the amount of Betawi language interference while qualitative used to describe forms of interference that are found. The sample data of this study is the short story  created by students from the Department of Education Indonesian Language and Literature which organized to fulfill the assigment of writing subject.The  results  obtained  in  this  study  as  follow:  1)  the  forms  of  interference  were found: the interference of word, affixation interference which include prefix, suffix, confix, and  the  repetition  of  the  word;  2)  The  amount  for  each  interference  that  occurs;  (a) Interference of suffix is most present in 23 (36.51%); (b) Interference in the category of prefix were 12 (19:05%), (c) interference in confix category were 9 or 14:28%, and (d) Interference  in  the  form  of  word  categories  were  19  (30.15%).  There  were  63 morphological interference from 36 students’ short stories.